Designing livestock interventions for emergency situations in Southern Africa - Freeman, H.A.; Kaitibie, S.; Moyo, Siboniso; Perry, Brian D. (International Livestock Research Institute, 2008)
This brief is a review of the research conducted by the International Livestock Research Institute (ILRI) and partners in Lesotho, Malawi and Zambia aimed to assess the contribution of livestock to livelihoods and its role in risk management. The objective of the study was to identify the livelihood assets and strategies of households, taking into account differences between men and women and the contexts that translate household capabilities into livelihood opportunities. The study suggests that there are marked differences in ownership of productive assets, in livelihood strategies and in vulnerability between men and women. The results of the study showed that households in southern Africa are exposed to a variety of shocks with cumulative impacts that can trigger an emergency. The main factors contributing to vulnerability to food insecurity include drought, widespread crop failure, animal diseases and declining access to livestock service delivery. These factors affect all households in a community but in different ways.